Novel:Mangal Waley Log, In the Context of the meaning of living - Dr. Muhammad Nasrallah (Zaban-o-Adab, 2024)
In this essay, the Novel: Mangal Waley Log, is analyzed in the perspective of the meaning of living. Any text is read indirectly to find the meaning of living; However, this book mainly presents the wisdom of living in the form of fiction. In view of the materialistic thinking of the present time, the problem of the true meaning of life has not been noticed; while this essay sheds light on the meaninglessness and meaning of life in the context of existential philosophy and the life of paralyzed , old character , who is aware of the news of his death. Despite facing the extremes of the darkness in his life, the Old wise man considers learning to die before dying and loving others to be the only logical thing in the world to truly live.